(untitled) (Balneo and PRM Research Journal, 2024)
(1) Background: The use of oxygen under pressure greater than atmospheric represents progress that can be measured in terms of importance with the introduction of blood transfusion and antibiotics in therapy. The aim of the research was to determine the impact of using a hyperbaric chamber (HC) on muscle, arterial saturation and heart rate.; (2) Methods: Twelve respondents who engaged in recreational exercise. HC Macy Pan O2 801 was used for oxygen delivery. Muscle saturation was assessed with the IDIAG Moxy device. Arterial saturation was monitored with an Omron OM-35 device, and intraventricular heart rate with a Polar FT2 device. All parameters were monitored before and after HC treatment for 50 min. and constant pressure of 2.5 ATA.; (3) Results: There was a significant increase in saturation in the pectoralis, p=.038, hamstring p=.042. In capillary saturation p=.008. Heart rate was reduced on average by about 8.5 beats p= .003. In the region of the latissimus do not record a statistically significant change in oxygen .060, however, numerical differences were determined.; (4) Conclusions: HC is an effective means of achieving positive physiological effects. It needs to be determined whether a higher ATA or duration of treatment gives better effects.